Hubungan Dukungan Keluarga Lansia dengan Pemanfaatan Posyandu Lansia di Wilayah Kerja Puskesmas Lembang - Nur Aisyah; Nur Anita; Muhrawi Yunding; Adnan Alqadri (Universitas Muhamadiyah Manado, 2024)
Posyandu for the elderly is a form of public health service that aims to improve the health and quality of life of the elderly. However, the utilization rate of Posyandu for the elderly is often not optimal. One of the influencing factors is family support. Family support is a form of assistance provided directly by the family to the elderly, including informational, emotional, instrumental, and appreciation. This study aims to determine the relationship between family support for the elderly and the utilization of Posyandu for the elderly. The design or method of this study uses an analytical survey design with a cross-sectional study method approach. The population in this study were elderly people who live in the Lembang Community Health Center Working Area with a sample of 80 respondents based on predetermined inclusion criteria. Data collection using questionnaires and observations. Univariate analysis is presented using a frequency distribution table while Bivariate analysis uses a chi-square test. The final result obtained a P value = 0.000 with a significant value of α = 0.005 through the Chi-square test. Since the P value <α, it is statistically concluded that there is a relationship between family support for the elderly and utilization of the Posyandu for the elderly in the Lembang Community Health Center work area. It is recommended that health workers be more active in providing education and motivation to elderly families regarding the importance of support in utilizing Posyandu for the elderly. Furthermore, health workers need to increase the socialization of Posyandu activities, conduct home visits for less active elderly people, and establish good communication with families so that they play a greater role in supporting elderly participation in Posyandu for the elderly.